SARS‐CoV‐2 infection and paediatric endocrine disorders: Risks and management considerations. Issue 3 (3rd June 2021) - Miller, Ryan; Ashraf, Ambika P.; Gourgari, Evgenia; Gupta, Anshu; Kamboj, Manmohan K.; Kohn, Brenda; Lahoti, Amit; Mak, Daniel; Mehta, Shilpa; Mitchell, Deborah; Patel, Neha; Raman, Vandana; et al.
Abstract: Background: Coronavirus‐19 (COVID‐19) is a disease caused by the SARS‐CoV‐2 virus, the seventh coronavirus identified as causing disease in humans. The SARS‐CoV‐2 virus has multiple potential pathophysiologic interconnections with endocrine systems, potentially causing disturbances in glucose metabolism, hypothalamic and pituitary function, adrenal function and mineral metabolism. A growing body of data is revealing both the effects of underlying endocrine disorders on COVID‐19 disease outcome and the effects of the SARS‐CoV‐2 virus on endocrine systems. However, comprehensive assessment of the relationship to endocrine disorders in children has been lacking. Content: In this review, we present the effects of SARS‐CoV‐2 infection on endocrine systems and review the current literature on complications of COVID‐19 disease in underlying paediatric endocrine disorders. We provide recommendations on management of endocrinopathies related to SARS‐CoV‐2 infection in this population. Summary and outlook: With the surge in COVID‐19 cases worldwide, it is important for paediatric endocrinologists to be aware of the interaction of SARS‐CoV‐2 with the endocrine system and management considerations for patients with underlying disorders who develop COVID‐19 disease. While children and adults share some risk factors that influence risk of complications in SARS‐CoV‐2 infection, it is becoming clear that responses in the paediatric population are distinct and outcomes from adult studies cannot be extrapolated. Evidence emerging from paediatric studies provides some guidance but highlights the need for more research in this area. Abstract : The SARS‐CoV‐2 virus has multiple potential pathophysiologic interconnections with endocrine systems. In this review, we present the effects of SARS‐CoV‐2 infection on endocrine systems and review the current literature on complications of COVID‐19 disease in underlying paediatric endocrine disorders. We provide recommendations on management of endocrinopathies related to SARS‐CoV‐2 infection in this population.